Model Pengembangan Agrowisata Yutaka Farm Desa Pasucen Trangkil Pati - Kholifah, Nor; Siswanto, Siswanto (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2024)
This study aims to analyze the development model of Yutaka Farm Agrotourism in Pasucen Village, Trangkil District, Pati Regency. This agrotourism site has successfully integrated environmental conservation, education, and local community empowerment through a sustainable tourism approach. Initially established as a plant nursery in 2017, Yutaka Farm has evolved into an agricultural-based tourist destination with a Japanese-themed concept, encompassing nature tourism, culinary experiences, and environmental education. Using a qualitative descriptive research method, this study found that Yutaka Farm's development through the stages of mapping, social planning, and social action has improved the local economy, community participation, and human resources quality. The implications of this model include enhancing the local community's quality of life, as well as preserving local culture and the environment. The success of Yutaka Farm demonstrates that a local wisdom-based agrotourism model can significantly impact economic and social development in rural areas.